Chromium, Cadmium, Nickel, and Lead in a Tropical Soil after 3 Years of Consecutive Applications of Composted Tannery Sludge - Santos, Jeova Lyra; Ferreira Araujo, Ademir Sergio; Pinheiro Leal Nunes, Luis Alfredo; Jacinto Oliveira, Mara Lucia; Melo, Wanderley Jose [UNESP] (Taylor & Francis Inc, 2014)
Agricultural use of tannery sludge (TS) may increase risks to soils. Thus, composting is recognized as one of the most suitable alternatives for TS recycling. Field experiments were carried out to evaluate the effects of composted tannery sludge (CTS) on chromium (Cr), cadmium (Cd), nickel (Ni), and lead (Pb) accumulation in soil after 3 years. Soil samples were collected 60 days after CTS application. After 3 years, The CTS increased Cr and Ni content, while Cd and Pb contents decreased. The third year, Cr contents showed linear increases as CTS rates were applied. The application of CTS, after 3 years, in the 2.5, 5, and 10 Mg ha(-1) increased Cr significantly (140.7%, 159.7%, and 19%, respectively) and Ni (32%, 53%, and 43.8%, respectively) contents in the soil surface layer. This means that consecutive amendments of CTS increase Cr contents in the soil and plants.
Keywords: Composting; Heavy metals; Industrial waste